SEM and XRD for removal of heavy metals from industrial wastewater and characterization of chicken eggshell. Issue 7 (7th April 2022) - Amin, Sumaira; Abbas, Moneeza; Tahir, Arifa; Ghani, Nadia; Abrar, Amina; Aslam, Fakhra; Ahmad, Safoora
Abstract: Heavy metal toxicity due to industrial wastewater has been a threat to the environment for the past many decades, especially in developing countries. Electroplating Industry wastewater containing heavy metals can become a serious environmental pollutant if not treated appropriately. Present study investigated the removal of nickel and chromium ions from electroplating wastewater using calcined hen eggshells because of it high removal capability, little cost and easy approachability. Characterization of the adsorbent such as proximate analysis, surface charge, X‐ray diffraction, and surface area was done prior to adsorption process. Batch adsorption experiment was performed to study the effect of different parameters such as adsorbent dose, contact time, temperature, and pH for adsorbent. Removal percentage of both heavy metals was checked by using calcined eggshell as adsorbent. Comparison was made between nickel and chromium to identify the most effective removal efficacy. It was concluded that utilization of natural waste was found suitable, easier, cost operative and environmental approachable for removal of heavy metals from industrial wastewater. Research Highlights: To use ecofriendly approach for the treatment of industrial wastewater. To used calcined eggshell as adsorbents for removing metal concentration from industrial wastewater. To find the metal removal potential of calcined eggshell under various environmental conditions like dosage, contact time, temperature, and pH. To checking the efficacy of calcined eggshell. Abstract : SEM and XRD of heavy metals